2008
DOI: 10.3354/esr00032
|View full text |Cite
|
Sign up to set email alerts
|

Home range, activity cycle and natal den usage of a female Sunda pangolin Manis javanica (Mammalia: Pholidota) in Singapore

Abstract: Here we present the first field report on the ecology of a single female Sunda pangolin and her young in their natural habitat on an offshore island of Singapore. Observations of this event were made possible by the use of radio-telemetry and infrared-triggered camera traps. Only one offspring was recorded from this birth event and the period of maternal care was approximately 3 to 4 mo. A total of 3 natal dens were used throughout the monitoring period, and hollows of large trees (> 50 cm diameter at breast h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 10 publications
3
59
0
3
Order By: Relevance
“…Short active periods have been reported for other nocturnal myrmecophagous species. For example, the Sunda pangolin (Manis javanica) is active for only 127±13 min day −1 (Lim and Ng, 2008). Camera trap data suggest that the giant anteater (Myrmecophaga tridactyla) is active during only 7 h of the day, less than for other mammals from a similar location (rodents, lagomorphs, ungulates and carnivores; Blake et al, 2012).…”
Section: Movement Ecologymentioning
confidence: 99%
“…Short active periods have been reported for other nocturnal myrmecophagous species. For example, the Sunda pangolin (Manis javanica) is active for only 127±13 min day −1 (Lim and Ng, 2008). Camera trap data suggest that the giant anteater (Myrmecophaga tridactyla) is active during only 7 h of the day, less than for other mammals from a similar location (rodents, lagomorphs, ungulates and carnivores; Blake et al, 2012).…”
Section: Movement Ecologymentioning
confidence: 99%
“…But the distinction between them is not absolute, the terrestrial pangolins also climb tree sometimes. For example, the field study on the ecology of a single female Malayan Pangolin and her young in their natural habitat proved that hollows of large trees were associated with all of their three dens (Lim and Ng 2007). Burrows are extremely important in the terrestrial pangolin’s life history because a suitable burrow could satisfy pangolin’s requirements for food sources, concealment and temperature, but only few studies about pangolin’s burrows were reported (Bao et al 2013; Jiang et al 1988; Liu and Xu 1981; Wu et al 2004b).…”
Section: Naturalistic Habitat For Captive Pangolinsmentioning
confidence: 99%
“…A pangolin of three kilogram can consume up to 300–400 g of termites per feeding (Coulson 1989; Lim 2008a). Different pangolin species have differences in their diet compositions.…”
Section: Dietary Husbandry Of Pangolinsmentioning
confidence: 99%
“…Trenggiling sebenarnya dapat hidup pada berbagai tipe habitat, mulai dari hutan primer, hutan sekunder, savana terbuka sampai perkebunan di sekitar pemukiman manusia (Lim & Peter Ng, 2007). Namun, informasi tentang tipe habitat dan sumberdaya habitat yang paling mempengaruhi/disukai trenggiling untuk bersarang dan mencari makan masih sangat sedikit.…”
Section: Pendahuluanunclassified